2021
DOI: 10.1126/sciimmunol.abe0531
|View full text |Cite
|
Sign up to set email alerts
|

Deep-sea microbes as tools to refine the rules of innate immune pattern recognition

Abstract: The assumption of near-universal bacterial detection by pattern recognition receptors is a foundation of immunology. The limits of this pattern recognition concept, however, remain undefined. As a test of this hypothesis, we determined whether mammalian cells can recognize bacteria that they have never had the natural opportunity to encounter. These bacteria were cultivated from the deep Pacific Ocean, where the genus Moritella was identified as a common constituent of the culturable microbiota. Most deep-sea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 74 publications
0
29
0
Order By: Relevance
“…Other LPS-interacting proteins have been described in detail in recent reviews 13 , 70 . Recently, it was shown that mammalian PRRs are unable to detect the LPS of most bacteria from a different ecosystem, such as deep sea bacteria, despite retaining most structural features of Escherichia coli LPS 71 . These data suggest that pattern recognition of structurally conserved ligands may be defined locally, not globally.…”
Section: Introductionmentioning
confidence: 99%
“…Other LPS-interacting proteins have been described in detail in recent reviews 13 , 70 . Recently, it was shown that mammalian PRRs are unable to detect the LPS of most bacteria from a different ecosystem, such as deep sea bacteria, despite retaining most structural features of Escherichia coli LPS 71 . These data suggest that pattern recognition of structurally conserved ligands may be defined locally, not globally.…”
Section: Introductionmentioning
confidence: 99%
“…Some variation in this detection efficiency originates from the co-evolution of PRRs and PAMPs structures. Specifically, some bacteria have evolved to produce less immunogenic PAMPs to avoid immune detection by their host (Fitzgerald and Kagan, 2020;Sansonetti, 2011;Wolf and Underhill, 2018), while PRRs have evolved to optimally recognize PAMPs of bacteria they typically encounter over microbes from remote ecosystems (Gauthier et al, 2021). In contrast, mechanosensing invasion by PIEZO1 makes it possible to identify a highly specific event of infection, which is fully restricted to certain pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of TLR response could be linked to the recent observation that TLR5, TLR8, TLR21, TLR22 and TLR23 are under positive selective pressure in Antarctic Notothenioids [41]. Furthermore, a study of deep-sea bacteria revealed pathogen associated molecular patterns (PAMPs) that failed to interact with human TLR, and this was explained by the absence of selective pressure for their recognition during pathogen-recognition receptors (PRR) evolution and so they were "immune silent" [123]. Nonetheless, although the transcriptional response of N. coriiceps to i.p.…”
Section: Discussionmentioning
confidence: 99%